Análise dos impactos dos veículos elétricos nos sistemas de distribuição considerando o modo V2G e o transporte de energia - Lazari, Gustavo Mores de (2020)
The aim of this master’s dissertation is to evaluate the insertion of electric vehicles (EVs) in a Distribution System through its energy charging and discharging modes. Motivated by the expansion of the EVs market and the reduction of carbon dioxide (CO2) emissions into the atmosphere, it is proposed a methodology that estimates the impacts of EVs on a Distribution System. For this purpose, urban mobility patterns are used to estimate the behavior of EVs and electricity demand curves to interpret the consumption patterns of a Distribution System. In this way, Vehicle-to-grid (V2G) and Vehicle-to-home (V2H) modes are explored. Furthermore, EVs charging and discharging strategies considering conventional tariff and white tariff are applied. To analyze the system is observed the electrical aspects related to the powers, voltages, and the electrical losses for the IEEE 13 Bars System through some scenarios using Open Distribution System Simulator (OpenDSS) and Matlab software. In the economic analyses, the yearly values of electricity consumption for the same scenarios are evaluated. In addition, the energy transport between the bars and the state of charge (SOC) of EVs batteries over the time are analyzed. Through the computer simulations, it is concluded that the programmed charging and discharging, especially considering the hourly demand of the bars, is the best option among the strategies. For the present study, charging in the commercial and industrial bars and discharging in the residential bars proved to be the most successfully scenario since it presented the smallest increases in electrical losses, the best indices in power quality parameters and the best results under the economic point of view.